“Development and Validation of Questionnaires to Assess Community Pharmacists’ Knowledge, Attitude, and Willingness to Practice (KawP) Vaccination Services: Advancing Immunisation Efforts” - Wakkundmath, Gangayya Jagadish; Ganachari, Madiwalayya Shivakantayya; Salimath, Geetanjali (International Journal of Pharmaceutical Investigation, 2026)
Background The presence of community pharmacists in the field is particularly important because they operate on the front line of contact with the population when providing the best health care. Evaluating their Knowledge, Attitude, and Practice (KAP) towards willingness to engage in professional responsibilities is essential for improving pharmacy services and public health outcomes. Materials and Methods This cross-sectional study involved several phases, starting with the design and development of a comprehensive questionnaire, followed by rigorous psychometric validation. An extensive literature review and consultations with experts ensured the questionnaire’s face and content validity. A pilot test with pharmacists refined the questions, while reliability was assessed using Cronbach’s alpha, and construct validity was evaluated through Exploratory Factor Analysis (EFA). Results The final questionnaire comprised 40 items distributed across three domains: Knowledge (13 items), Attitude (12 items), and Practice (15 items). With Cronbach’s alpha coefficients ranging from 0.9068 to 0.9418, it demonstrated strong internal consistency, while exploratory factor analysis confirmed its construct validity with a clear factor structure. Conclusion This reliable and user-friendly instrument, termed the Knowledge, Attitude, and Willingness to Practice (KAwP) questionnaire, effectively assesses community pharmacists’ willingness to practice. It is a valuable tool to identify knowledge gaps, enhance attitudes, and improve pharmacy practices through targeted research and training interventions.
Keywords: Community pharmacists; Immunisation; Pharmacy Practice; Questionnaire; Reliability; Vaccination; Validation.